Modified metal oxides supported on polyvinyl chloride catalysts for the photodegradation of paraquat dichloride - Wan Noralwani Wan Zamry, 1987-; Rusmidah Ali; Wan Azelee Wan Abu Bakar; Fakulti Sains (2013)
Thesis (Sarjana Sains (Kimia)) - Universiti Teknologi Malaysia, 2013